Self-Representation among Dark-Skinned Individuals on the Discourse of Beauty - Larasati, Hasty (Masyarakat: Jurnal Sosiologi, 2018)
This article will explore how dark-skinned individuals perceive their skin color and whether they categorize their appearance as beautiful or ugly. Until recently, the dominant perception of beauty in Indonesia was represented by fair-skinned people, and this fact is strongly related to an individual’s identity. Dark skin is considered less beautiful. However, some individuals attempt to counteract the dominant beauty discourse. Previous literature studies found two reasons that support the counter-discourse toward beauty: recognition and negotiation. Recognition is an act of countering the mainstream discourse, while negotiation is an attempt to contest one’s identity based on their skin. This article argues that women can counter the dominant discourse based on negotiation, because individuals have free choice, body autonomy, and bargaining power. This article is written based on a qualitative research, with in-depth interviews conducted with nine female informants who have attempted to counter the mainstream beauty discourse.